Development of integrating spiritual model into dietetics practice among dietitian in the east coast of Peninsular Malaysia - Aflah Afandi (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2021)
Chronic disease patients often express their burden of illness to the dietitians because they need spiritual comfort. However, due to the lack of time, skills, and knowledge in spirituality, it may be challenging for the dietitian to provide spiritual support, but some manage to address the needs. By using a pragmatism philosophical approach and Islamic worldview, this study aimed to examine dietitians' experience with integrating spirituality during nutrition counselling. The specific objectives were to, 1) synthesis current literature on issues with religion/spirituality in nutrition and dietetic research, 2) identify attitudes of dietitian towards spiritual inquiry and their values on spirituality, 3) explore Islamic spiritual conversation during nutrition counselling, and 4) create a model for integrating Islamic spiritual care in dietetics practice. In general, this study has three components including integrative review, e-survey, and focus group. It started with an integrative review using samples of articles published up to 2018 from selected databases. Then, followed by a concurrent cross-sectional e-survey (quantitative) and focus group (qualitative) between May to December 2019. This concurrent study is known as convergent mixed methods study design. Participants were recruited among the members of Malaysian Dietitians' Association for the e-survey (N=128) using volunteer sampling through their official Facebook page. Besides, the study interviewed selected Muslim dietitians (N=28) working within the East Coast of Peninsular Malaysia in six focus group discussions using snowball sampling. For the analysis, the integrative review used descriptive and meta-synthesis. The survey adopted descriptive analysis, Pearson's chi-square test, and factor analysis. Meanwhile, data from the focus group was analysed using thematic content analysis. Cross-analysis of data from the esurvey and focus group had enabled the study to interpret merged integrated data through joint displays approach. As the results, regardless of religious affiliation, more than half of the dietitians reported have ever inquired about patients' spiritual needs, but only 2% always willingly made the inquiry. Talking about spirituality might promote inner strength and gave meaning to dietitians' self-spirituality. The study identified several themes that emerged for dietitians' experiences with Islamic spiritual conversation. The final spiritual care model identified three possible approaches that always willingly made spiritual inquiry, only when the patient asked, and never inquire. This study concludes that 1) spirituality play an important role in dietary selfmanagement of diabetic patients, 2) small proportion of Malaysian dietitian are always willingly making a spiritual inquiry, 3) Islamic spiritual conversation during nutrition counselling are evident among Muslim dietitians, 4) a new model for integrating Islamic spiritual care in dietetics practices may offer immediate response to a patient with spiritual distress. The practical implication of the study demonstrated that spiritual conversations might promote a holistic approach in dietetic patient-centred care practices.